IMPLEMENTING QUESTION-ANSWER RELATIONSHIPS (QAR) STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION SKILL - Fuad Abdul Baqi (ENGLISH, 2019)
This action research was conducted to highlight how far the improvement of students’ reading comprehension skill after being treated by implementing QAR strategy and to find out the advantages when QAR is implemented in teaching reading comprehension. The research was organized at SMA Negeri 1 Rangkasbitung, Lebak - Banten. The subject of the research was the eleventh grade students, class IPS3. The design of it was an action research by covering three cycles, and every cycle consists of five meetings. Planning, acting, observing, and reflecting were implemented in every cycle to get a clear data. The research applied two sorts of data collecting: qualitative and quantitative data. Observation, recording, and interview were conducted to obtain qualitative data, while the quantitative data was gained through test. The research finding reflected that implementing Question-Answer Relationship (QAR) Strategy can help students in comprehending the text while answering the questions. The students were able to categorize the questions as well to avoid spending too much time while finding the answer. The implementation of QAR Strategy in teaching-learning process was getting better cycle to cycle, the students were energetic, active, enthusiastic, and felt much more confident to take a part in reading learning activity eventually. It showed that teacher’s teaching strategy had positive impact to students’ reading comprehension, and could arouse students’ motivation and participation as well to learn which greatly influenced their reading comprehension skill. It is helpful for teacher as a framework for directing questioning activities and comprehension instruction in pre-, while-, and post-reading. Implementing QAR in reading comprehension can ensure that it does not only focus on lower-level skills and question but in high level as well and it can motivate students to think critically and creatively.  Considering QAR is helpful and beneficial for both teacher and students, the institution may implement QAR for any grades and school subjects in order to make students familiar with higher-level question. Therefore, it will be no longer difficult to comprehend the text for students who have been treated by implementing QAR.